Characterization of multiplicative integer problems posed by future teachers (Educação e Pesquisa, 2022)
Assuming that teachers must be able to formulate school problems, this study deals with the approach of multiplicative problems of integers. Thus, this article focuses on the characterization of multiplicative problems of integers posed by future Spanish elementary teachers. To do this, we have analyzed problems formulated by 121 students of the Primary Education Degree - prospective teachers – at the University of Huelva, who were asked to pose problems in whose resolution the operation 8x(-2) had to be carried out. To delve into the characteristics, a content analysis was made of each of the problems, covering four aspects: the semantic category they belong to, coordination of the terms used in the formulation with the demanded, context it is set within, and problem solvability. The results of the study show that prospective teachers indistinctly propose problems of structures based on isomorphisms of measure and scalar relation, while experiencing difficulties in formulating the requirement of the problem in such a way that the solution explicitly maintains its negative nature. These results have potential implications for teacher training, which should promote, based on its curricular proposals, the capacity of future teachers to pose mathematical problems.